Clinical Evaluation of Prochlorperazine Risk / Benefit in Emergency Department Patients Receiving I.V Tramadol - Abdul- Razzaq Mshiemish, Bahir (Journal of the Faculty of Medicine Baghdad, 2011)
Background: antiemetics are commonly prescribed as prophylactic for nausea and vomiting when opiates analgesics are prescribed in the emergency department.Objective: to assess the incidence of nausea and vomiting after tramadol analgesia, and the effect of prochlorperazine on this incidence.Patients and methods: I.V tramadol was administered with prochlorperzine (group I) or pyridoxine (group II) to 44 patients with acute sever pain.Results: the incidence of nausea and vomiting was not significant between patient groups; while the occurance of extrapyramidal side effects was only seen in the prochlorperazine group. The low incidence of nausea and vomiting after opiate analgesic and higher incidence of side effects with prochloperazine are consistent with controlled data in literature.Conclusion: prophylactic prochlorperazine should not be used routinely in emergency department for patients receiving narcotic analgesia.